Design and Implementation of Knowledge Management, Learning Organizations and Learning Experience Based on LMS Corporate University - Yassir, Muhammad; Muid N, Abd. (Universitas Muhammadiyah Surakarta, 2024)
Corporate University is a system that combines Knowledge Management (KM), Learning Organization (LO) and Learning Experience (LE). Therefore, the existence of software media is needed. This research aims to design, implement, and test Learning Management System (LMS) based on Corporate University. This LMS is built with web-based technology with Java and PHP programming languages, and MySQL database. The method used is agile scrum with stages that include Product Backlog, Sprint Backlog, Sprint, and Working Increment of The Software. This research found a software in the form of an LMS specifically designed and built according to the needs of Corporate University by integrating KM, LO, and LE in a 70:20:10 pattern. The instrument testing stage was carried out using the Pearson product moment validity test and Cronbach alpha reliability test. The function testing stage is carried out using the black box testing method, and for user satisfaction is carried out with questionnaires and questionnaires using frequency analysis, percentage, average, and standard deviation. The results of black box testing show that this LMS can work as expected. This is reinforced by the results of frequency and percentage analysis, as many as 84% of respondents were satisfied overall. While the mean value and standard deviation for each question given to respondents are above 4.0, indicating a high level of satisfaction. In conclusion, this research makes a significant contribution in the field of technology-based learning system development, especially in the context of Corporate University. By integrating KM, LO, and LE, this research offers a more comprehensive LMS model that fits the needs of modern organisations.